Situational crime analysis of poaching within Territorial Use Rights Fisheries (TURFs) - Vallejos, Tomás; Nahuelhual, Laura; Gelcich, Stefan; Oyanedel, Rodrigo (Frontiers in Marine Science, 2024)
Illegal, unreported, and unregulated (IUU) fishing poses a significant threat to marine resource management globally. Environmental criminology play a vital role in understanding and mitigating IUU activities by focusing on contextual elements surrounding these crimes. This study examines the dynamics of poaching within areas managed through Territorial User Rights for Fisheries (TURFs), with a specific emphasis on the loco (Concholepas concholepas) fishery in Chile. Employing Crime Script Analysis (CSA) as the primary methodological lens, this research meticulously deconstructs the criminal process involved in TURFs poaching operations. Through CSA, the study identifies key actors, tactics, and facilitators, providing a comprehensive understanding of poachers modus operandi. Additionally, by integrating CSA with Situational Precipitators of Crime (SPC), critical factors are identified, such as environmental conditions, socio-economic disparities, and enforcement weaknesses shaping poaching opportunities within TURFs. The analysis reveals a complex interplay between SPC factors, underscoring their role in shaping poaching dynamics. Building upon these findings, the study proposes a comprehensive Situational Crime Prevention (SCP) framework aimed at effectively combating TURFs poaching. It emphasizes the importance of striking a careful balance between restrictive and inclusive measures to mitigate potential negative consequences. In conclusion, this study contributes valuable insights into understanding and addressing IUU fishing, particularly within TURFs in Chile. By leveraging environmental criminology.